PELAKSANAAN PENYIDIKAN TINDAK PIDANA PERDAGANGAN ORANG OLEH PERWIRA UNIT PENYIDIK UNIT PELAYANAN PEREMPUAN DAN ANAK DI KEPOLISIAN DAERAH RIAU - Debora, Pricilia Irene; A, Syaifullah Yophi; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In writing this paper, the authors discuss the implementation of the criminal investigations of human trafficking by Perwira Unit Penyidik Unit PPA Polda Riau. Writing in background mode the background by the affluance of trafficking in persons especially women and children are very diverse, ranging from the promised jobs, kidnapping victims, debt bondage and deception. The purpose of this thesis is to investigate the implementation of criminal investigations of trafficking in persons and know the obstacles faced by Panit Idik Unit PPA and solutions in the implementation of criminal investigations of human trafficking. In this thesis, the writer uses sociological research methods. Nature of the research used is descriptive, providing a clear picture of the implementation of the criminal investigations of trafficking in persons by Panit Idik Unit PPA Polda Riau. Results of qualitative research conducted by analysis and use deductive method, the decomposition problem from general spesific. From the reseearch it can be concluded that the obstacles faced by the Perwira Unit Penyidik Unit PPA in that implementation of the investigation is divided into internal factors and external factors.Internal factors consists of less cost factor, a factor that is less infratructure and personel factors are insufficient in number.External factors consists of factors of vitims and people who still do not understand the importance of law in the implementattion process of ivestigation.Keyword: Implementation – Investigations – Panit Idik – Unit PPA – Criminal offense of trafficking in persons